Modelling the utilization of cloud health information systems in the Iraqi public healthcare sector - Meri, Ahmed; Hasan, MK; Danaee, Mahmoud; Jaber, Mustafa; Jarrar, Mu'taman; Safei, Nurhizam; Dauwed, Mohammed; Abd, Sura K.; Al-bsheish, Mohammed (Elsevier, 2019)
The Iraqi healthcare sector has been suffering from health records management issues from the perspectives of low information technology integrity and data complexity. As a solution, cloud computing services can offer an alternative, low-cost, and reliable way to store, manage, and retrieve health-related data, as well as monitoring patients’ health conditions anywhere and anytime using any device with any platform. The migration to cloud services is not yet widespread in Iraqi health facilities due to various challenges, including security and privacy, legal policies, and implementation. For instance, there has been no research shedding light on the utilization of cloud computing services in Iraqi hospitals’ health information systems. This study proposed a model by defining the critical success factors influencing physicians’ confirmation and behavioral control toward utilizing cloud health information systems in Iraqi hospitals. The model's variables were statistically investigated by utilizing an online questionnaire. Data were collected from a probability sample of 259 physicians working in four Iraqi high-IT hospitals. The collected ordinal data were analyzed using the PLS-SEM approach as a nonparametric second-generation multivariate analysis. The results showed that the effects of system compatibility, system complexity, security, and privacy on physicians’ confirmation and behavioral control were statistically significant. Both confirmation and behavioral control had a positive effect on physicians’ utilization of the technology in the Iraqi hospitals. It is believed that such finding may help to aid the current understanding of cloud health systems in managing health data as well as providing the necessary recommendations for policy makers to direct healthcare professionals to continuously consider the use of modern information and communications technology in the workplace.